Analisis Butir Soal sebagai Standarisasi Mutu Sekolah Dasar pada Mata Pelajaran PAI dengan Menggunakan Pendekatan Rasch Model di SD Ma’arif NU Kecamatan Pandaan Pasuruan - Askhabul Kirom; Mochamad Hasyim (Universitas Yudharta Pasuruan, 2021)
Comprehensive tests aim to improve the quality of assessment to determine the item's level of difficulty, know the level of conformity of the item (item fit), and know the existence of biased question items. Explorative, descriptive research is a post-hoc diagnosis described as a retro-fitting approach. The strengthening method is carried out by analyzing question items and grain response data to find quality information about students in the final semester 1 of Islamic Religious Education subjects in the 2020/2021 school year. The study's findings are as follows: 1. The difficulty level of the item measure seen in S14 question item of the Measure value is +2.82, and only 25 students answer correctly. 2. The level of conformity of the item question (item fit) there is one response that is outside the boundary of the Outfit trust room that is in the item question S14, other than the item of the question has met the criteria of outfit z-standard, outfit means-square value, and point measure correlation. 3. Detection of biased question items found in question item S13, where the item question S13 probability value is 0.02, which is below 5% (0.05).